(1322) experimental optimization by stimulation technique التحسين التجريبي بتقنية التحفيز - khopshid, motaz (The Institute Of National Planning., 2018)
the attractive features that computer simulation offers, have encourage operation researchers and statisticians to improve its practice through the use of various statistical techniques to analyse the obtained results.